The Role Of Institutions And E-government In Mobilizing Value-Added Tax Revenue In Asia-Pacific Mid-Size Economies - Wijaya, Suparna; Hashfi, Hasbiul (WIM Solusi Prima, 2024)
This study examines how the informal economy, law enforcement, and e-government interact to affect value-added tax (VAT) revenue in middle-income countries in Asia Pacific in the period 2002-2018. Panel data regression analysis is used to estimate this relationship. The results show that the informal economy significantly reduces VAT revenue, while e-government implementation has a negative effect. E-government dampens the negative impact of informality on revenue. However, it strengthens the negative relationship between law and revenue, contrary to expectations. These findings underscore the importance of balanced tax reforms that take into account country-specific constraints. The expansion of e-governance should be accompanied by capacity building and efforts to reduce the informal economy. This study makes an empirical contribution by examining the joint impact of informality, governance, and technology on tax performance in developing countries.